Photographs of AIDS: Doctors and Homosexuals in the Costa Rican Press (1985-1990) - Jiménez Bolaños, José Daniel (2018)
The article proposes an analysis of the photographs that were included in the news related to HIV / AIDS between 1985-1990 in the newspaper La Nación. A contextualization about the emergence of HIV / AIDS worldwide and in Costa Rica is made. The theoretical perspective of Barthes about photographic analysis is used, and three categories are established to address the material: AIDS as a natural disaster and a military vanguard, the representation of medical knowledge, and the politics of shame. Among the main results we can find the problematization of the link between photography and text to produce specific connotations; the masculine protagonism within the medical knowledge, and a transformation of the aesthetics of homosexuality, shifting from an exoticism to a concealment by shame. As a conclusion, insult and shame, and their relationship with visual representations, are fundamental axes that allow us to address the issue of HIV / AIDS.